Leukocyte Telomere Length Is Related to Brain Parenchymal Fraction and Attention/Speed in the Elderly: Results of the Austrian Stroke Prevention Study - Gampawar, Piyush; Schmidt, Reinhold; Schmidt, Helena (Frontiers in Psychiatry, 2020)
There are controversial results if leukocyte telomere length (LTL) is related to structural brain changes and cognitive decline in aging. Here, we investigated the association between LTL and 1) global MRI correlates of brain aging such as brain parenchymal fraction (BPF) and white matter hyperintensities (WMH) load and Fazekas score as well as 2) global (g-factor) and domain specific cognition such as attention/speed, conceptualisation, memory, and visuopractical skills. In total, 909 participants of the Austrian Stroke Prevention Study with LTL, MRI and cognitive tests were included. There were 388(42.7%) men, the mean age was 65.9 years. Longer LTL was significantly associated with larger BPF (β=0.43, p<0.001), larger WMH load (β=0.03, p=0.04), and score (β=0.05, p=0.04) after adjusting for age, sex, vascular risk factors and ApoE4 carrier status. The effect on BPF was more significant in the subgroups of women (β=0.51, p=0.001), age >65 years (β=0.58, p=0.002), BMI≥25 (β=0.40, p=0.004), education ≤10 years (β=0.42, p=0.002), hypertensives (β=0.51, p=0.001), cardiovascular disease (CVD) (β=0.58, p=0.005) , non-diabetics (β=0.42, p<0.001) and Apoe4 non-carriers (β=0.49, p<0.001). The effect on WMH was significant within the hypertensives (load: β=0.04, p=0.02), non-diabetics (load:β=0.03, p=0.01; score: β=0.06, p=0.02 ), in those with education ≤10 years (load: β=0.03, p=0.04; score: β=0.07, p=0.02) , in ApoE4 non-carriers (load: β=0.03, p=0.02; score: β=0.07, p=0.01) and in subjects without CVD (score: β=0.06, p=0.05). We only observed a significant association between LTL and the cognitive domain of attention/speed, which was confined to the subgroups of BMI≥25 (β=0.04, p=0.05) and education ≤10 years (β=0.04, p=0.05). The effect of LTL on attention/speed was partly mediated in both subgroups by BPF (β=0.02, 95%CI= 0.01:0.03) when tested by bootstrapping. Our results support a strong protective role of longer LTL on global brain volume which in turn may contribute to better cognitive functions especially in the attention/speed domain in the elderly.